The Effect of Free Shipping on Purchasing Decisions at GoFood - Herdianti, Putri Yasmin (International Journal Administration, Business & Organization, 2023)
The purpose of this study was to investigate the impact of free shipping promotions on the purchasing decisions of Bandung State Polytechnic students, Indonesia using OFD GoFood. The study implements a descriptive quantitative research method and employs a survey questionnaire for data collection. The sample size of this study comprises 100 respondents. Additionally, the data are analyzed using descriptive and regression analysis techniques. The study indicated that free shipping positively impacts purchasing decisions made through OFD GoFood among students of Bandung State Polytechnic, Indonesia.